Research Trends: Dye Sensitized Solar Cell Sebagai Sumber Energi Terbarukan Ramah Lingkungan - Fareka (UNISTEK, 2026)
Currently, petroleum is a main energy source used to meet the world?s needs. However, petroleum is an energy that has the potential to decrease over time. Besides that, sunlight can be used to reduce petroleum energy consumption. Solar energy is a form of renewable energy. Dye Sentisized Solar Cell (DSSC) is a technology for converting light energy into electricity. However, the efficiency value obtained from DSSC is still small. A lot of research related to DSSC has been carried out. In the period 2020-2024, there were 59 articles related to DSSC on Google Scholar which had more than 36 citations. The most articles related to DSSC were published in 2021, namely 22 articles. Meanwhile, the highest number of citations for articles related to DSSC was in 2020, namely 2424 citations. The research topic that has been widely developed is modification of light-sensitizing substances in DSSCs. The review result combination of superior modifications that have been successfully carried out by previous research on each component in the DSSC is expected to increase efficiency value to meet the world's energy needs.